Mobile Application for Carrel Reservation (MACR) in UUM Library - Shatnawi, Bander Ali (2009)
Mobile device and the emergence of wireless technologies are rapidly increasing, in the contemporary world, providing application for libraries. The UUM library use a manual process for carrel reservation, this process needs time and effort from the students. Most universities in the world have techniques to do reservation in the library via the web site. Therefore, this study propose to design mobile application for carrel reservation as %88 of Malaysian people have mobile phone (Malaysia Communication and Multimedia Commission, 2007), the study will develop an application and a prototype to use mobile device to facilitate the reservation process.